Distribution and Frequency of the kdr Mutation V410L in Natural Populations of Aedes aegypti (L.) (Diptera: Culicidae) From Eastern and Southern Mexico. Issue 1 (29th August 2019) - Villanueva-Segura, Olga K; Ontiveros-Zapata, Kevin A; Lopez-Monroy, Beatriz; Ponce-Garcia, Gustavo; Gutierrez-Rodriguez, Selene M; Davila-Barboza, Jesus A; Mora-Jasso, Esteban de J; Flores, Adriana E
Abstract: Aedes aegypti (L.) is the primary vector of the viruses that cause dengue, Zika, and chikungunya, for which effective vaccines and drugs are still lacking. Current strategies for suppressing arbovirus outbreaks based on insecticide use pose a challenge because of the rapid increase in resistance. The widespread and excessive use of pyrethroid-based insecticides has created a large selection pressure for a kdr-type resistance, caused by mutations in the para gene of the voltage-gated sodium channel ( vgsc ). Our objective was to evaluate the allelic frequency of natural populations of Ae. aegypti of Mexico at codon 410 of the para gene. Twenty-six Ae. aegypti populations from east and southern Mexico were genotyped for the codon 410 using allele-specific PCR. The frequencies of the L410 allele in Ae. aegypti ranged from 0.10 to 0.99; however, most of the frequencies were in the range of 0.36 to 0.64. The highest frequencies were found in three populations from the state of Veracruz, namely, Minatitlan with 0.99, Poza Rica with 0.82, and Jose Cardel with 0.97, along with populations from Cancun in Quintana Roo with 0.93, Frontera in Tabasco with 0.91, and Ciudad del Carmen in Campeche with 0.86. The frequency of the L410 allele was high in all populations of Ae. aegypti with higher values in populations of the southeast of the country. The knowledge of specific substitutions in vgsc and their interaction to confer resistance is essential to predict and develop future strategies for resistance management in Ae. aegypti in Mexico.